New Challenges of the Information Content in Ukraine - H. HOLUBOVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The author examines the historical background regarding the formation and development of the information services market as a major catalyst for the development of the information society. The level of development of information activity in the leading countries of the world is the result of a long historical process of evolutionary and revolutionary transformations.The study describes the information services market as an economic space where the interests of producers and consumers of these services are realized. The principles of functioning of the information services market are described and market participants are highlighted.It is determined that the information market operates a quality resource – information. Information activity is described as an infrastructure branch of the economy and its functions and tasks are described. Depending on the type of information, the information services market consists of the following sectors: business information, specialist information, consumer information, information systems and facilities.The current state of development of the information society in Ukraine is analyzed, in particular, the number of Internet users in 2019 amounted to 26.1 million against 2.8 million people in 2009 the use of social media as a communication platform is justified. The largest share of enterprises used social media as social networks – almost 45.0%, 22.3% – business websites, 20.3% – other knowledge sharing tools and 12.4% – business blogs. The most active users of social networks were enterprises with activities related to wholesale and retail trade – 26.6%, manufacturing enterprises – 23.0% and construction – 9.2%. The main purpose of businesses to use social media is to promote them and promote their products.The author describes the goals and challenges of the digital industry, as well as the role of statistics in the field of statistical support, ensuring the completeness of statistical databases and monitoring the processes occurring in information content.